If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 18 = 8(u + -3) + -2u Reorder the terms: 18 = 8(-3 + u) + -2u 18 = (-3 * 8 + u * 8) + -2u 18 = (-24 + 8u) + -2u Combine like terms: 8u + -2u = 6u 18 = -24 + 6u Solving 18 = -24 + 6u Solving for variable 'u'. Move all terms containing u to the left, all other terms to the right. Add '-6u' to each side of the equation. 18 + -6u = -24 + 6u + -6u Combine like terms: 6u + -6u = 0 18 + -6u = -24 + 0 18 + -6u = -24 Add '-18' to each side of the equation. 18 + -18 + -6u = -24 + -18 Combine like terms: 18 + -18 = 0 0 + -6u = -24 + -18 -6u = -24 + -18 Combine like terms: -24 + -18 = -42 -6u = -42 Divide each side by '-6'. u = 7 Simplifying u = 7
| (5m-10)(m+4)=0 | | -6=2x+2(x+3) | | c(200)=6.2x+10100 | | 15+12/2= | | X+8=76 | | -10n+4=-86 | | (5+7i)(4-12i)= | | -11x+12=-7x | | 86900=-19.2+2.4x | | y+7=8(x-1) | | 9+3x+12=8x-9-5x | | 7y+6(y-4)=2 | | c(200)=6.2+10100 | | 3x-2(8-2x)=5 | | 2x=2+-14 | | X-0.75=1.00 | | 6=2(y-7)-7y | | 3-5k=88 | | 6+-x=1 | | h-25=2h-8 | | m-1=96 | | 8(-8x-6)=6x-22 | | 2n+n-6=30 | | -4=(v+1) | | -34=8u+2(u+7) | | 1.9(1.6+3.7)= | | 2(x*7)=5(x-7) | | 5(z-1)=(4z+4) | | (x-3)=(6x-2) | | X+11x-2=0 | | 2(x-2)+14=10x+5-4x | | 36x^2+25=60 |